2017
DOI: 10.1155/2017/3502438
|View full text |Cite
|
Sign up to set email alerts
|

Pathologic and Radiologic Correlation of Adult Cystic Lung Disease: A Comprehensive Review

Abstract: The presence of pulmonary parenchymal cysts on computed tomography (CT) imaging presents a significant diagnostic challenge. The diverse range of possible etiologies can usually be differentiated based on the clinical setting and radiologic features. In fact, the advent of high-resolution CT has facilitated making a diagnosis solely on analysis of CT image patterns, thus averting the need for a biopsy. While it is possible to make a fairly specific diagnosis during early stages of disease evolution by its char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 82 publications
(180 reference statements)
0
16
0
Order By: Relevance
“…To date, the number of solitary cystic lung cancers reported in the English-language literature is not large, and the most recent references are case reports and small case reviews (7,(14)(15)(16)(17)(18). In this series, the most common pathologic types of solitary cystic lung cancer were adenocarcinoma (81 [87.1%] of 93), but in situ adenocarcinoma is rare (14).…”
Section: Pathologic Basismentioning
confidence: 84%
“…To date, the number of solitary cystic lung cancers reported in the English-language literature is not large, and the most recent references are case reports and small case reviews (7,(14)(15)(16)(17)(18). In this series, the most common pathologic types of solitary cystic lung cancer were adenocarcinoma (81 [87.1%] of 93), but in situ adenocarcinoma is rare (14).…”
Section: Pathologic Basismentioning
confidence: 84%
“…testing (PFT) shows restrictive physiology with reduced FVC and FEV1, elevated FEV1/FVC and reduced total lung capacity. Typical CT findings of thin-walled, predominantly midzoned perivascular cysts associated with ground-glass attenuation and centrilobular nodules in a nonsmoker is highly suggestive of LIP [1,4]. Other frequent imaging findings include bilateral bronchovascular and interlobular septal wall thickening with lower lobe predilection.…”
Section: Discussionmentioning
confidence: 99%
“…ere is currently no consensus on first-line therapy for LIP, as controlled clinical trials have not yet been reported. e latest therapeutic regime consists of corticosteroids alone versus immunoglobulin therapy modification or cytotoxic drugs [4,8]. Further complicating matters include LIP in the presence of commonly associated immunodeficiency syndromes such as rheumatoid disease, HIV infections and dysgammaglobulinemia in which immunosuppressive agents may further exacerbate opportunistic infections.…”
Section: Discussionmentioning
confidence: 99%
“…Cystic lung disease such as Langerhans cell histiocytosis or lymphocytic interstitial pneumonia can present bizarre shaped lung cysts in adults. 16 17 However, those diseases are very rare in childhood. 18 In the present study, bizarre lung cysts were more frequently observed in children than adults after cessation of similar exposure to HD in the same room, even if adults demonstrated chronic, typical centrilobular nodules.…”
Section: Discussionmentioning
confidence: 99%